Peace and war in territorial disputes - Herschel I. Grossman (Brown University, Department of Economics, 2004)
Why do sovereign states sometimes fail to settle territorial disputes peacefully? Also, why do even peaceful settlements of territorial disputes rarely call for the resulting border to be unfortified? This paper explores a class of answers to these questions that is based on the following premise: States can settle a territorial dispute peacefully only if (1) their payoffs from a peaceful settlement are larger than their expected payoffs from a default to war, and (2) their promises not to attack are credible. This premise directs the analysis to such factors as the advantage of attacking over both defending and counterattacking, the divisibility of the contested territory, the possibility of recurring war, the depreciation or obsolescence of fortifications, and inequality in the effectiveness of mobilized resources. – credibility ; fortifications ; counterattacks ; divisibility ; recurring war ; depreciation
Keywords: D74; H56; 330; Public Choice; Friedensforschung; Politischer Konflikt